PAEDIATRIC VISION CARE: DOING THE RIGHT THINGS VS DOING THINGS RIGHT - Chen, Ai Hong (International Journal of Allied Health Sciences, 2021)
Research thinking mind enhance paediatric vision care practice. Current challenges in paediatric vision care practice will be included. The importance of professional learning in paediatric vision care will be discussed. The difference between doing the right things and doing things right in shaping the future of paediatric vision care will be elaborated. Also incorporate personal sharing of paediatric optometry research development and direction.